Combination of natural silica and alumina sources for synthesis of MCM-22 zeolite - Tanwongwan, Worapak; Chollacoop, Nuwong; Faungnawakij, Kajornsak; Assabumrungrat, Suttichai; Nakhanivej, Puritut; Eiad-ua, Apiluck (My University, 2023)
Zeolite has become a promising material that can potentially play a pivotal role in resolving environmental crises. Among zeolite families, MCM-22 zeolite shows outstanding intrinsic properties associated with the topology and porous structure, offering ion-exchange advantages for catalytic activity processes. The synthesis of MCM-22 zeolite becomes challenging when concerning the cost and catalytic performance. To overcome this bottleneck, we demonstrate a sustainable route of a hydrothermal process using natural resources as starting materials. Rice husk from agricultural waste was used as a silica source while natural clays (kaolin and bentonite) were applied as alumina sources. The products from natural sources were compared with the use of commercial starting materials, e.g., NaAlO2 (for alumina) and Na2SiO3 and TEOS (for silica), in points of crystal, compositional, and morphological views. We showed that the high purity of MCM-22 zeolite can be obtained from rice husk silica (RHS) and aluminosilicate gel (ASG) extracted from kaolin, while the use of ASG extracted from bentonite tended to be unsuitable to generate the zeolite formation. We also studied the effects of reaction time and the ratio of RHS/ASG on the crystallinity and surface area of MCM-22. The architecture and acidity of an optimal product were explored by Nuclear magnetic resonance spectroscopy and Temperature-programmed desorption of ammonia, demonstrating the success of achieving well acidity.
Keywords: Hydrothermal; MCM-22; Natural clays; Rice husk silica; Zeolite